Finance and Development, September 1975. (Finance and Development; Finance and Development ;, 1975)
This paper describes the need for a new framework for international resource transfers. The paper highlights that the only international deal that presently exists on resource transfers is enshrined in the acceptance by the rich nations of a target of 1 percent of gross national product, with 0.7 percent as official development assistance on fairly concessional terms. However, the acceptance of this target by rich nations was grudgingly slow, and the actual performance has been most disappointing.